Effects of acid-basic treatments of date stones on lead (II) adsorption. Issue 11 (24th July 2019) - Boudrahem, Farouk; Aissani-Benissad, Farida; Audonnet, Fabrice; Vial, Christophe
ABSTRACT: The effect of acid-basic treatments of date stones on lead adsorption was investigated. The physicochemical properties of this low-cost adsorbent were characterized by N2 adsorption and mass titration. The date stones sample, treated with HNO3, possess the highest surface oxygen containing functional groups (2.1 mmol/g), surface area (115 m 2 /g), and pore volume (0.048 cm 3 /g) and the more adsorption capacity to the lead(II) ions. The effect of contact time, initial concentrations of adsorbate, ionic strength, and adsorbent dose on the uptake of lead was studied in batch experiments. The sorption process was found to follow Redlich-Peterson isotherm and pseudo-second-order rate kinetics.